THE INFLUENCE OF HUMAN RELATIONS AND THE WORKING ENVIRONMENT TOWARDS EMPLOYEE WORK ETHIC : Case Study at the South Coast District Inspectorate - Koslendra, Endang; Susanti, Febsri (LPPM Universitas Bina Bangsa, 2022)
This study aimed to analyze and prove the influence of human relations and work environment on employee work ethics in the Inspectorate Office of Pesisir Selatan District. The sampling technique used is saturated sampling, while the number of samples used for analysis is 47 people. The data analysis technique used to test the hypothesis is multiple linear regression. In this study, there are two independent variables: human relations and work environment. Based on the results of multiple linear regression analysis, it was found that the human relations variable has a positive and significant effect on work ethic, work environment has a positive and significant effect on work ethic, and human relations and work environment simultaneously has a positive and significant effect on Employee Work Ethics in the Inspectorate Office of Pantai Selatan District. South. This study provides practical recommendations to the Inspectorate Office of Pesisir Selatan District to continue to improve work ethic in the future